Out‐of‐hospital ketamine: review of a growing trend in patient care - Bryan B. Kitch (Journal of the American College of Emergency Physicians Open)
Abstract Ketamine is a unique medication with a long history of use in the emergency department. Out‐of‐hospital indications for ketamine have been explored and are currently expanding in some systems. This article provides background on ketamine history and pharmacology, its use in the hospital environment and possible applications for emergency medical services usage of this medication. Contraindications and adverse reactions are discussed to provide education on the nuances of ketamine administration and mitigation strategies. Out‐of‐hospital indications for ketamine are discussed including airway management, rapid sequence induction, analgesia, sedation, and treatment of excited delirium.